INFLUÊNCIA ANTRÓPICA NA GEOQUÍMICA DE ÁGUA E SEDIMENTOS DO RIO CONCEIÇÃO, QUADRILÁTERO FERRÍFERO, MINAS GERAIS - BRASIL - Parra, R. R.; Roeser, H. M. P.; Leite, M. G. P.; Nalini Jr., H. A.; Guimarães, A. T. A.; Pereira, J. C.; Friese, K. (Geochimica Brasiliensis, 2012)